A dataset for vascular plant diversity monitoring for the natural World Heritage site on Amami‐Oshima Island, Tokunoshima Island, and the northern Okinawa Island. Issue 5 (19th July 2022) - Toyama, Hironori; Totsu, Kumiko; Tagane, Shuichiro; Aiba, Shin‐ichiro; Ugawa, Shin; Suzuki, Eizi; Yamazaki, Kaito; Fuse, Kengo; Takashima, Atsushi; Toyama, Nariko; Kadoya, Taku; Takeuchi, Yayoi
Abstract: This data paper presents the vascular plant biodiversity sampled from four plots on Amami‐Oshima Island, three plots on Tokunoshima Island, and one plot on Okinawa Island within the natural World Heritage site, and an additional three plots in southern Kyushu using the standardized belt‐transect survey method during July 2012 to October 2020. The dataset includes 99 families, 215 genera, and 381 species of vascular plants, and provides species occurrence among 10 subplots for all vascular plants, girth at breast height (GBH) and height of all trees and climbers with GBH ≥ 3.2 cm or height ≥ 4 m in each 5 × 100 m plot. This dataset serves as baseline data for subsequent plant diversity monitoring of the natural World Heritage site. The Darwin Core Archive is deposited in the Global Biodiversity Information Facility (GBIF) through the Japan Initiative for Biodiversity Information, and are thus accessible through the GBIF portal under the Creative Commons Attribution 4.0 International license. The detailed Metadata for this abstract published in the Data Article section of the journal is available in MetaCat in JaLTER at http://db.cger.nies.go.jp/JaLTER/metacat/metacat/ERDP‐2022‐03.1/jalter‐en . Abstract : A dataset for vascular plant biodiversity sampled from four plots on Amami‐Oshima Island, three plots on Tokunoshima Island, and one plot on Okinawa Island within the natural World Heritage site, and an additional three plots in southern Kyushu using the standardized belt‐transect survey method.